E-ELEARNING DALAM MENINGKATKAN KOMPETENSI MENGAJAR DOSEN DI PERGURUAN TINGGI DI KOTA MEDAN - Harahap, Seprida Hanum; Alpi, Muhammad Firza (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
This research show about the use of internet as learning media to improving teaching competence at universities in Kota Medan. It is expains how the internet can be used as learning media on teaching and learning process when the class activities begin and improve teaching competence. The benefit of this research is expected to improve lecturers teaching competence based on the theoretical study of information technology-based learning media by internet-based website used at universities in Kota Medan. This research is descriptive qualitative where it will reveal facts and circumstances that occur at the time of lecturing activities conducted lecturer subjects in the faculty of economics at the universities in Kota Medan. The population of this research consists of three universities in Kota Medan consist of Univesitas Muhammadiyah Sumatera Utara, Universitas Negeri Medan and Universitas Harapan Medan with the object of research is the lecturer from the college which the population of 80 lecturers from 100 questionnaires that have been distributed. Based on the pedagogical results of the questionnaire of the teacher respondents, it was found that 83% of the teachers gave the teaching with good pedagogic results, while the competence for teachers for internet use as a learning media found that only 63% of 80 respondents who internet used as learning media.Keywords : Learning Media, Internet, Website, E-Learning.